2020
DOI: 10.3803/enm.2020.35.2.367
|View full text |Cite
|
Sign up to set email alerts
|

Achievement of LDL-C Targets Defined by ESC/EAS (2011) Guidelines in Risk-Stratified Korean Patients with Dyslipidemia Receiving Lipid-Modifying Treatments

Abstract: Background: This study assessed the proportion of risk-stratified Korean patients with dyslipidemia achieving their low-density lipoprotein cholesterol (LDL-C) targets as defined by the European Society of Cardiology/European Atherosclerosis Society (ESC/ EAS) (2011) guidelines while receiving lipid-modifying treatments (LMTs). Methods: In this multicenter, cross-sectional, observational study, we evaluated data from Korean patients aged ≥19 years who were receiving LMTs for ≥3 months and had an LDL-C value wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 33 publications
0
10
0
1
Order By: Relevance
“…The difficulty in managing this very high-risk group was also reported in a recent study in South Korea, which showed that high-intensity statins were prescribed to only 9.1% of patients with very high risk, with 61% of these patients not achieving the LDL-c goal of <1.8 mmol/L. 37 ) Suboptimal doses of statins were observed in several Asian countries in the DYSIS-II study, 38 ) mainly due to concerns about the side effects of higher statin doses satisfaction with patients’ LDL-c levels. 39 ) Our findings highlight the gap between clinical practice and existing guidelines, in that statin utilization remains inadequate, thus contributing to not achieving LDL-C goals.…”
Section: Discussionmentioning
confidence: 60%
“…The difficulty in managing this very high-risk group was also reported in a recent study in South Korea, which showed that high-intensity statins were prescribed to only 9.1% of patients with very high risk, with 61% of these patients not achieving the LDL-c goal of <1.8 mmol/L. 37 ) Suboptimal doses of statins were observed in several Asian countries in the DYSIS-II study, 38 ) mainly due to concerns about the side effects of higher statin doses satisfaction with patients’ LDL-c levels. 39 ) Our findings highlight the gap between clinical practice and existing guidelines, in that statin utilization remains inadequate, thus contributing to not achieving LDL-C goals.…”
Section: Discussionmentioning
confidence: 60%
“…Previous studies showed that the LDL-C target goal attainment rate for Korean patients with T2DM was less than 50% [17][18][19][20]. Compared to previous studies with low LDL-C target goal achievement of 17.6% for very-high risk and 47.2% for high risk groups, the recent LDL-C target goal attainment rate has improved.…”
Section: Discussionmentioning
confidence: 87%
“… 26 When assessing the gap between real-world practice and clinical guidelines, investigators’ assessment of risk was underestimated by 71.6% compared to that by clinical guidelines. 27 Physicians’ perceptions of the target achievement rate of LDL-C were higher than the actual achievement rate (70.6% vs. 47.4%), 28 and physician satisfaction with patients’ LDL-C levels was the primary reason for the non-intensification of statin therapy. 27 …”
Section: Current Status Of Lipid Management In Korean Patients With T2dmmentioning
confidence: 98%
“… 27 Physicians’ perceptions of the target achievement rate of LDL-C were higher than the actual achievement rate (70.6% vs. 47.4%), 28 and physician satisfaction with patients’ LDL-C levels was the primary reason for the non-intensification of statin therapy. 27 …”
Section: Current Status Of Lipid Management In Korean Patients With T2dmmentioning
confidence: 98%